The Estimation of Resistivity of Poka Alluvial Plain Material by Geoelectric Method with Wenner-Schlumberger Configuration - Latupapua, Andrias Izaac; Tahapary, Fahrul Dadan; Soplanit, Rudy (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study was conducted to determine the lateral and vertical distribution of material resistivity values on Poka alluvial plain using electrodes with Wenner-Schlumberger configuration. Mapping is carried out on 2 lines each 120 m long with the smallest space of 10 m. The results showed that the resistivity of the material ranged from 48.8 Ωm to 2.247 Ωm spread laterally with a depth of up to 26.2 m. Loose Sand material occupies the upper layer, followed by the Alluvium and Sand layers in the middle, and Sand and Water which are unconfined aquifers in the lower layer.